SDG space: Revealing the structure and complementarities among sustainable development goals in China - Mimi Gong; Ke Yu; Changchang Zhou; Zhouyi Liu; Zhenci Xu; Ming Xu; Shen Qu (Fundamental Research)
To achieve the United Nations Sustainable Development Goals (SDGs) by 2030, it is essential to understand the interlinkages between the goals. Previous research has investigated these interactions by focusing on their correlations. However, few studies have systematically prioritized them from a structural perspective through the complementarity measurements and empirically validated their policy effectiveness, such as which goals and indicators impact other SDGs most, especially in China. This study introduces a new concept known as the ‘SDG space’ by employing the “Product Space” approach in network science and economics. It measures the complementarities between SDGs and indicators through their network structures in investigating effective policy design. Using the most recent available but unpublished data for 31 Chinese provinces, the SDG space was constructed at the 17 SDG and 118 indicator levels by analyzing the probability of comparative advantage between each SDG or indicator pair co-occurring in the same place. Historical data confirm that in the ‘SDG Space’ network, a goal connected to other well-developed goals would enjoy better future growth and vice versa. The structure reveals that SDG 4 (Quality Education), 15 (Life on Land), and 1 (No Poverty) are critical goals with transformative synergies to other SDGs. Furthermore, we identified strong complementarities between land-based ecosystems and clean water and climate actions using the finer-grained indicator-level space. These findings help pave the way for China toward a sustainable future by providing science-based policy recommendations for decision-makers. They can be generally applied to other countries and regions to assist in navigating toward sustainable development.